Effect Of Tamarillo (Solanum Betaceum Cav.) Addition On Physical And Chemical Characteristics Of Yoghurt Produced - Novelina Novelina (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2024)
Yoghurt is one of the milk-based fermented products, adding fruit juice to yoghurt is part of product innovation, expected to improve quality and consumer liking. This study aims to determine the effect and level of addition of tamarillo juice (Solanum betaceum Cav.) on the characteristics of yoghurt produced. This study used a complete randomized design (CRD) method with 5 treatments and 3 replicates. Data were analyzed using analysis of variance (ANOVA) and Duncan's New Multiple Range Test (DNMRT) at the 5% level. The treatment in this study was the addition of tamarillo juice as much as 0% (A), 5% (B), 10% (C), 15% (D), 20% (E). The results showed that the addition of tamarillo juice to yoghurt had a significant effect on viscosity, color, fat content, ash content, total solids, total lactic acid, and Organoleptic test (color, aroma, taste and consistency), but had no significant effect on protein content, pH value and total lactic acid bacteria. The best formulation was in treatment E (addition of 20% tamarillo juice) with an average viscosity value of 13.03 Cp; color 83.73 oHue (Yellow red); protein content 4.11%; fat content 3.29%; ash content 0.59%; total solids 19.17%; total lactic acid 1.04%; pH value 4.52; total lactic acid bacteria 2.3x109CFU/g ; color 4.3 (like); aroma 4.25 (like); taste 4.15 (like) and consistency 4.25 (like).